ANALISIS DISTRIBUSI SARANG PENYU HIJAU Chelonia mydas DI PULAU JEMUR RIAU - Yustina '; Suwondo '; Arnentis '; Yuspen Hendri (Program Studi Pendidikan Biologi, 2004)
A surveys of three station along the nesting beach for distribution nesting analysis with beach characteristics and microclimatic nesting green turtles Chelonia mydas in Pulau Jemur-Riau was conducted in April- July 2002. The spatial distribution along the nesting beach namely the nesting abundant at highest the beach slope are 24°-31°, the grain sizes are medium sand (MZ = 2,18) and coarse sand (MZ =1,34). Temporary distribution in the nesting begins in April, extends through May and June, and decreases during July. The coral stones are limiting factor for landing beach success. The characteristic of nesting (beach slope) indicate microclimatic effect on nesting and impacted for distribution was reducing abundant of nesting. Canopy vegetation at highest beach slope are 30° had microclimatic effect on nesting. Key words : Distribution, microclimatic, nesting, green turtles, Pulau Jemur